ANALISIS PERPAJAKAN SEBELUM DAN SETELAH PENERAPAN SISTEM BADAN LAYANAN UMUM (BLU) TERHADAP ADMINISTRASI PERPAJAKAN DAN TINGKAT KEPATUHAN WAJIB PAJAK (Studi Kasus UIN Syarif Hidayatullah Jakarta) - Ay Maryani (Esensi: Jurnal Bisnis dan Manajemen, 2014)
The purpose of this study was to describe differences in the administration of the taxation system and assess the level of taxpayer compliance and the impact on administration of the taxation and taxpayer compliance level at UIN Syarif Hidayatullah Jakarta before and after applying the system of Public Service Agency. This research is a case study conducted using descriptive method with qualitative approach. These results indicate the general impact there are differences in the administration of the taxation system and taxpayer compliance level from the application of Public Service Agency positive impact on the administration of the tax administration and taxpaye compliance level.DOI: 10.15408/ess.v4i2.1958